Labor Market Polarization and Intergenerational Mobility: Theory and Evidence - Jan-Luca Hennig (ZBW - Leibniz Information Centre for Economics, 2021)
In this paper I investigate the causal relationship between labor market polarization and intergenerational mobility, two of the most important features of advanced labor markets in recent decades. The former relates to the disappearance of middle-wage routine jobs and the rise of both high- and low-income jobs. The latter measures the cross-generational link between the income of parents and that of their children. To understand the implications of polarization on economic mobility, I develop a model that accounts for labor market polarization, spatial heterogeneity and intergenerational mobility. Specifically, I incorporate the task framework into an overlapping generations model, which models education choice as a function of parental bequests and future wages. The main predictions from the model encompass limited upward mobility for children from low-income parents if replacement of routine labor is high, and educational polarization for younger generations. I test the model predictions exploiting various data sources for the United States. Empirical analyses provide evidence for lower upward mobility for children from low-income parents, higher intergenerational elasticity for children whose parents work in manual occupations, and for educational polarization of young labor market entrants.
Keywords: J21; J23; J24; J62; O33; R23; 330; Labor Market Polarization; Intergenerational Mobility; Educational Choice; Local Labor Markets